Effect of salinity on germination and emergence of seven forage species - Lastiri Hernández, Marcos Alfonso; Álvarez Bernal, Dioselina; Soria Martínez, Luis Humberto; Ochoa Estrada, Salvador; Cruz Cárdenas, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2017)
In the Ciénega de Chapala región, portion of Michoacán most of the forage crops are the main sustenance of the traditional livestock systems. However, water scarcity and increasing salinity are the main limiting environmental factors that directly affect both its establishment and development. In this research, the ability of germination and emergence of seven forage species was evaluated in in vitro conditions, when exposed to different concentrations of NaCl. The evaluation was carried out in a period of 21 days, in which the seeds were placed in an incubator without light at a temperature of 25/17 °C (day/night) respectively. Acid digestion method was used for the removal of Na+, K+, Ca2+ and Mg2+ cations from the germinated seedlings. Salinity treatments were 0.0 mM, 50 mM; 100 mM; 200 mM and 400 mM. In the imbibition stage a differential response was observed between species under conditions of saline stress, mainly at 200 and 400 mM, producing a drastic reduction in the absorption levels with respect to its own controls and later reflected in its germinative capacity. H. vulgare and L. perenne species showed a lower K+/Na+ ratio, confirming to be more tolerant to this level of salt concentration.
Keywords: cation content; Ciénega de Chapala; salt stress; sodium chloride